Conocimientos sobre el consumo de ácido fólico en gestantes y puérperas usuarias del Hospital Universitario de Motupe - Uchuari Maza, Mariuxi Mireya (2019)
Folic acid is B9 vitamin that helps the body to create new cells, it is considered an essential nutrient, which means that the human being is not able to synthesize it. This micronutrient plays an important role in pregnancy, where she has influence on fetal growth and development. Folic acid deficiency prior to conception and early pregnancy may increase the risk of developing congenital malformations. The goal of this research was to determine the knowledge of the consumption of folic acid of pregnant women and post-natal women who attend the University Hospital of Motupe during the period October 2018-April 2019. The study is cross-sectional, descriptive and quantitative, the sample was of 208 pregnant and post-natal women who received a survey. The results obtained were entered in the SPSS program V.24, reaching the conclusion that most of the participants were of legal age, married, with an average of 2 children, engaged in domestic chores and with secondary education, was captured the same number of pregnant and post-natal women; the largest proportion of them were in the third trimester of gestation and late puerperium, respectively. Regarding the knowledge about folic acid, 71.2% of the participants presented deficient knowledge, however, 63.9% consumed it. Given these circumstances, an intervention plan was developed whose purpose was to strengthen knowledge about the importance of preconceptional and prenatal folic acid intake. Keywords: Folic acid, knowledge, gestation, puerperium.